The fear of beggars: stewardship and poverty in Christian ethics - Johnson, Kelly S. (The Eerdmans Ekklesia series, 2007)
Introduction: waking up lost -- Begging and Christian economy -- The irony of voluntary begging -- Stewardship : the rehabilitation of humility -- The insolence of human wretchedness -- Reaping what was sown -- Why not be a beggar? Peter Maurin and viator economics -- Conclusion: economic comedy